PENERAPAN METODE ROLE PLAYING DALAM MENINGKATKAN HASIL BELAJAR SISWA KELAS V TERHADAP MATERI IPAS DI UPT SDN 26 PAINAN SELATAN - Safitri, Miza; Safrudin, Safrudin (STKIP Pesisir Selatan, 2025)
National education is carried out by individuals as an effort to transform towards the overall development of Indonesia through physical and mental activities. Education functions as a concrete action to improve human activities for the better, with education, existing problems will gradually be overcome and can also improve the quality of human life. This study applies a classroom action research approach. The purpose of this research is to evaluate ways to support the improvement of science learning outcomes, especially in the understanding sector, with a reflective, participatory, and collaborative approach in the application of science learning using a role-playing model, which has an impact on children's activities, class dynamics, as well as challenges and problems that arise throughout the science teaching process in the classroom. To achieve this goal, there are four main stages that form the CAR cycle, including planning, implementation, observation, and reflection. The findings of this research are an increase in children's learning outcomes who use the application of the role-playing method for science material at UPT SDN 26 Painan Selatan.